Key mutations in the C-terminus of the HBV surface glycoprotein correlate with lower HBsAg levels in vivo, hinder HBsAg secretion in vitro and reduce HBsAg structural stability in the setting of HBeAg-negative chronic HBV genotype-D infection. Issue 1 (1st January 2020) - Salpini, Romina; Battisti, Arianna; Piermatteo, Lorenzo; Carioti, Luca; Anastasiou, Olympia E.; Gill, Upkar S.; Di Carlo, Domenico; Colagrossi, Luna; Duca, Leonardo; Bertoli, Ada; La Rosa, Katia Yu; Fabeni, Lavinia; et al.
ABSTRACT: Increasing evidences suggest that HBsAg-production varies across HBV-genotypes. HBsAg C-terminus plays a crucial role for HBsAg-secretion. Here, we evaluate HBsAg-levels in different HBV-genotypes in HBeAg-negative chronic infection, the correlation of specific mutations in HBsAg C-terminus with HBsAg-levels in-vivo, their impact on HBsAg-secretion in-vitro and on structural stability in-silico . HBsAg-levels were investigated in 323 drug-naïve HBeAg-negative patients chronically infected with HBV genotype-D( N = 228), -A( N = 65) and -E( N = 30). Genotype-D was characterized by HBsAg-levels lower than genotype-A and -E (3.3[2.7–3.8]IU/ml; 3.8[3.5–4.2]IU/ml and 3.9[3.7–4.2]IU/ml, P < 0.001). Results confirmed by multivariable analysis correcting for patients'demographics, HBV-DNA, ALT and infection-status. In genotype-D, specific C-terminus mutations (V190A-S204N-Y206C-Y206F-S210N) significantly correlate with HBsAg<1000IU/ml( P -value from <0.001 to 0.04). These mutations lie in divergent pathways involving other HBsAg C-terminus mutations: V190A + F220L (Phi = 0.41, P = 0.003), S204N + L205P (Phi = 0.36, P = 0.005), Y206F + S210R (Phi = 0.47, P < 0.001) and S210N + F220L (Phi = 0.40, P = 0.006). Notably, patients with these mutational pairs present HBsAg-levels 1log lower than patients without them( P -value from 0.003 to 0.02). In-vitro, the above-mentioned mutational pairs determined a significant decrease in HBsAg secretion-efficiency compared to wt( P -value from <0.001 to 0.02). Structurally, these mutational pairs reduced HBsAg C-terminus stability and determined a rearrangement of this domain. In conclusion, HBsAg-levels in genotype-D are significantly lower than in genotype-A and -E in HBeAg-negative patients. In genotype-D, specific mutational clusters in HBsAg C-terminus correlate with lower HBsAg-levels in-vivo, hamper HBsAg-release in-vitro and affect its structural stability, supporting their detrimental role on HBsAg-secretion. In this light, genotypic-testing can be a valuable tool to optimize the clinical interpretation of HBsAg in genotype-D and to provide information on HBV-pathogenicity and disease-progression.